The Primordial and Acosmic Aspect of Typhon in Theogony - Baglioni, Igor (Richtmann Publishing, 2010)
The research was able to observe how the words used by Hesiod systematically describe Typhon as a hybrid uncontrollable entity, characterized by ubri , and by a great power, expressed in furious violence. In particular, it could be observed how the ofiomorfic appearance of the entity, as well as the voices emitted from its many heads, qualify its distinctive features, both for the immeasurable size and polymorphia, and for its emotional instability, driven by uncontrollable impulses and unable to domain its passions. This aspect reflects perfectly the opposition to Zeus, the deity who, over the tale told in the Theogony, qualifies himself for his connections to, which the mhti